2019
DOI: 10.4103/jnrp.jnrp_166_18
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Yield and Complication of Frameless Stereotactic Brain Biopsy

Abstract: Background:With the advancement of neuronavigation technologies, frameless stereotactic brain biopsy has been developed. Previous studies proved that frameless stereotactic brain biopsy was as effective and safe as frame-based stereotactic brain biopsy. The authors aimed to find the factors associated with diagnostic yield and complication rate of frameless intracranial biopsy.Materials and Methods:Frameless stereotactic brain biopsy procedures, between March 2009 and April 2017, were retrospectively reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 17 publications
0
20
0
1
Order By: Relevance
“…According to the literature, diagnostic yield and procedure-related complications are not significantly different between framebased and frameless brain biopsies. Table 1 summarizes the results of recent reports investigating the safety and diagnostic yield of frameless stereotactic biopsy [6,[25][26][27][28][29][30][31][32][33][34]. The frame-based technique provides a diagnostic yield of 81.3-99.2%, while the diagnostic yield of frameless stereotactic brain biopsy has been presented to range between 89% and 99.3% for various techniques [7,33,35,36].…”
Section: Clinical Results Of Accuracy and Safetymentioning
confidence: 99%
See 2 more Smart Citations
“…According to the literature, diagnostic yield and procedure-related complications are not significantly different between framebased and frameless brain biopsies. Table 1 summarizes the results of recent reports investigating the safety and diagnostic yield of frameless stereotactic biopsy [6,[25][26][27][28][29][30][31][32][33][34]. The frame-based technique provides a diagnostic yield of 81.3-99.2%, while the diagnostic yield of frameless stereotactic brain biopsy has been presented to range between 89% and 99.3% for various techniques [7,33,35,36].…”
Section: Clinical Results Of Accuracy and Safetymentioning
confidence: 99%
“…The volume or size of the biopsied lesion is a vital component affecting diagnostic yield. One clinical study found that a lesion diameter of > 3 cm is essential in predicting diagnostic yield, while small lesions were associated with postoperative hematoma [6]. On the other hand, the reported meta-analysis results are unlikely to be applicable to lesions < 1 cm in maximal diameter [37].…”
Section: Clinical Results Of Accuracy and Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Characterization of the IDH mutation status has therefore become imperative prior to treatment selection and patient stratification [8]. However, this still relies on invasive tissue sampling and analysis, harboring inherent limitations, including post-operative complications and sample error [9]. The non-invasive classification of gliomas based on imaging was proposed as an alternative to this approach, leading to the identification of imaging features as correlates to molecular subtypes.…”
Section: Introductionmentioning
confidence: 99%
“…Taweesomboonyat et al . presented their experience in frameless stereotactic brain biopsy in their article: “Diagnostic yield and complication of frameless stereotactic brain biopsy.”[1]…”
mentioning
confidence: 99%